Paradigm Shifts in Economic Theory and Policy - Laurie Laybourn-Langton; Michael Jacobs (Intereconomics, 2018)
In most countries, mainstream economic policy has not yet undergone any significant change, and there is little consensus on what, if anything, ought to replace it. However, there are some signs of an emerging transition, at several levels.
Keywords: 330